A Fiberglass and Resin Post Technique Combined with Fragment Collage of an Upper Central Incisor: Multidisciplinary Treatment - Ramírez Barrantes DDS, MSD, PhD, Juan Carlos (2018)
The clinical treatment of anterior tooth fractures requires specialized knowledge, technical skill, and a degree of artistic sense to ensure successful treatment. Herein, we describe the reattachment of an original tooth fragment with endodontic involvement via the utilization of a micro-hybrid composite resin and an aesthetic fiberglass post.